Nondestructive Investigation of Heterojunction Interfacial Properties Using Two-Wavelength Raman Spectroscopy on Thin-Film CdS/CdTe Solar Cells. Issue 9 (September 2016) - Zeng, Guanggen; Harrison, Paul; Kidman, Ali; Al-mebir, Alaa; Feng, Lianghuan; Wu, Judy
Raman spectra specific to CdS and CdTe were obtained on the CdS/CdTe heterojunction interface by employing two excitation wavelengths of λ1  = 488 nm and λ2  = 633 nm, respectively, from the glass side of Glass/FTO/CdS/CdTe/HgTe:Cu:graphite/Ag solar cells fabricated using pulsed-laser deposition (PLD). This two-wavelength Raman spectroscopy approach, with one wavelength selected below the absorption edge of the window layer (λ2 in this case), allows nondestructive characterization of the CdS/CdTe heterojunction and therefore correlation of the interfacial properties with the solar cell performance. In this study, the evolution of the interfacial strain relaxation during cell fabrication process was found to be affected not only by the inter-diffusion of S and Te corresponding to the formation of CdS x Te 1–x ternary alloy with a various x from ∼0.01 to ∼0.067, but also by the variation in misfit dislocations (MDs) at CdS/CdTe interface from Raman TO/LO ratio ∼2.85 for as-deposited sample to TO/LO ∼4.44 for the cells post treatment. This is consistent with the change of the Urbach energy from 0.03 eV to 0.09 eV, indicative of the deterioration of crystalline quality of CdTe at interface although improved CdTe crystalline quality was observed away from the interface after the CdCl2 annealing. This difference crucially impacted on the rectification characteristics of the CdS/CdTe heterojunction and therefore the solar cell performance.